2021
DOI: 10.3390/jcm10081561
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Breastfeeding and Cosleeping on Early Childhood Caries: A Cross-Sectional Study

Abstract: The type and duration of breastfeeding can be key factors in the development of early childhood caries (ECC). The association between nighttime feeding and ECC was investigated. Specifically, whether cosleeping is a potential mediator of children’s oral health was investigated, considering many of the etiological factors of caries. In this cross-sectional study, 212 children (aged 2–4 years) from Madrid (Spain) who breastfed at night were examined to assess the mean decayed/filled primary teeth (dft) index, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
7
0
3
Order By: Relevance
“…Moreover, it was found that infants who continued to breastfeed for 18 months or more, nevertheless sleeping independently without continuous breastfeeding at night, had a relatively lower rate of dental caries than those who co-slept. 40…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it was found that infants who continued to breastfeed for 18 months or more, nevertheless sleeping independently without continuous breastfeeding at night, had a relatively lower rate of dental caries than those who co-slept. 40…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was found that infants who continued to breastfeed for 18 months or more, nevertheless sleeping independently without continuous breastfeeding at night, had a relatively lower rate of dental caries than those who co-slept. 40 Kubota et al 46 also explained that among child-rearing factors, breastfeeding, and night-time breastfeeding after 18 months were significantly associated with ECC. Achmad et al 37 reported that the caries number was 75.2% in the group which breastfed for more than 12 months.…”
Section: Breastfeeding Practices and Eccmentioning
confidence: 97%
See 1 more Smart Citation
“…18 aydan daha az anne sütü alanlarda dmft'in daha düşük olduğunu; 18 aydan fazla ve geceleri sık emzirmenin ise çürük risk faktörü olduğunu bildirmişlerdir. 47 Chanpum ve ark., anne sütüyle beslenmiş 9-18 aylık 513 çocuk ve annesinde gerçekleştirdikleri çalışmada dişler plak ve çürük açısından incelenmiş, annelerin emzirme davranışları ve çocukların oral hijyen alışkanlıkları anket aracılığı ile sorgulanmış; plak skorları yüksek olan ve emzirilerek uykuya dalan çocuklarda EÇÇ görülme oranının daha yüksek olduğu, çürük oluşumunda en önemli faktörün ise dental plak miktarı olduğu belirtilmiştir. 48 Devenish ve ark., 2-3 yaş grubu 2181 çocukta yaptıkları çalışmada, dmft değerleri ölçülmüş ve 3, 6, 12, 24 ayda anne sütüyle beslenme alışkanlıkları, 1 yaş sonrası şeker alımı ve sosyodemografik faktörler anket ile sorgulanmıştır.…”
Section: Kök Hücrelerunclassified
“…Thus, the influence of infant diet on the development of the oral microbiome should be considered. Such studies are crucial in light of the unresolved question on whether prolonged breastfeeding duration is causative of dental caries ( Iida et al, 2007 ; Nobile et al, 2014 ; Chaffee et al, 2015 ; Devenish et al, 2020 ; Carrillo-Diaz et al, 2021 ), necessitating high quality data to inform feeding decisions for parents.…”
Section: Introductionmentioning
confidence: 99%